The effects of five dietary lipid sources on growth, body composition and antioxidant parameters of the clamworm, Perinereis aibuhitensis. (25th April 2017) - Lv, Fu; Nie, Qing; Wang, Tian; Wang, Aimin; Yang, Wenping; Liu, Fei; Yu, Yebing; Lv, Linlan
Abstract: The clamworm Perinereis aibuhitensis is a commercially important polychaete in China, but knowledge about the nutritional demands of this species is limited. In this study, the effects of five lipid sources in the diet, namely fish oil (FO), soyabean oil (SO), rapeseed oil (RO), cottonseed oil (CO) and mixed vegetable oil (MO), on growth, whole‐body composition and antioxidant parameters of juvenile P. aibuhitensis were evaluated. The results showed that clamworms fed the CO diet had higher specific growth rate (SGR) and protein efficiency ratio (PER) than the other treatments. The accumulation of longer‐chain polyunsaturated fatty acids (PUFAs) was observed in P. aibuhitensis, suggesting that P. aibuhitensis had the ability to elongate and desaturate PUFAs with 18C to form longer‐chain PUFAs. The values of n‐3/n‐6 in clamworms fed vegetable oil diets (ranged from 0.20 to 0.31) were much closer to the recommended values for human food compared with FO diet (2.47). Analysis of the antioxidant parameters revealed that clamworms fed the CO diet suffered lower peroxidation burden than those fed FO diet. These results suggested that cottonseed oil is a suitable lipid source for P. aibuhitensis feeds.